Novel Hydraulic Vulnerability Proxies for a Boreal Conifer Species Reveal That Opportunists May Have Lower Survival Prospects under Extreme Climatic Events - Rosner, Sabine; Světlík, Jan; Andreassen, Kjell; Børja, Isabella; Dalsgaard, Lise; Evans, Robert; Luss, Saskia; Tveito, Ole E.; Solberg, Svein (Frontiers in Plant Science, 2016)
Top dieback in 40-60 years old forest stands of Norway spruce (Picea abies (L.) Karst.) in southern Norway is supposed to be associated with climatic extremes. Our intention was to learn more about the processes related to top dieback and in particular about the plasticity of possible predisposing factors. We aimed at (i) developing proxies for P50 based on anatomical data assessed by SilviScan technology and (ii) testing these proxies for their plasticity regarding climate, in order to (iii) analyze annual variations of hydraulic proxies of healthy looking trees and trees with top dieback upon their impact on tree survival. At two sites we selected ten tree pairs, i.e. one healthy looking tree and one tree with visual signs of dieback such as dry tops, needle shortening and needle yellowing (n = 40 trees). Vulnerability to cavitation (P50) of the main trunk was assessed in a selected sample set (n = 19) and we thereafter applied SilviScan technology to measure cell dimensions (lumen (b) and cell wall thickness (t)) in these specimen and in all 40 trees in tree rings formed between 1990 and 2010. In a first analysis step, we searched for anatomical proxies for P50. The set of potential proxies included hydraulic lumen diameters and wall reinforcement parameters based on radial, mean and tangential tracheid diameters. The conduit wall reinforcement based on tangential hydraulic lumen diameters ((t/bht)²) was the best estimate for P50. It was thus possible to relate climatic extremes to the potential vulnerability of single annual rings. Trees with top dieback had significantly lower (t/bht)² and wider tangential (hydraulic) lumen diameters some years before a period of water deficit (2005-2006). Radial (hydraulic) lumen diameters showed however no significant differences between both tree groups. (t/bht)² was influenced by annual climate variability; strongest correlations were found with precipitation in September of the previous growing season: high precipitation in previous September resulted in more vulnerable annual rings in the next season. The results are discussed with respect to an “opportunistic behavior” and genetic predisposition to drought sensitivity.